Forum Rules: Read This Before Posting


Topic: How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?  (Read 866 times)

0 Members and 1 Guest are viewing this topic.

Offline AussieKenDoll

  • Regular Member
  • ***
  • Posts: 41
  • Mole Snacks: +0/-0
How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?
« on: December 19, 2018, 11:26:33 PM »
How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?

Offline AussieKenDoll

  • Regular Member
  • ***
  • Posts: 41
  • Mole Snacks: +0/-0
How to derive ΔG∘=−RTlnKeq from basic thermodynamic principles?
« Reply #1 on: December 19, 2018, 11:28:08 PM »
How to derive ΔG∘=−RTlnKeq from basic thermodynamic principles?

Offline Borek

  • Mr. pH
  • Administrator
  • Deity Member
  • *
  • Posts: 24877
  • Mole Snacks: +1628/-395
  • Gender: Male
  • I am known to be occasionally wrong.
    • Chembuddy
Re: How to derive ΔG∘=−RTlnKeq from ΔG∘= ΔH∘-T ΔS∘?
« Reply #2 on: December 20, 2018, 03:07:34 AM »
I have merged your threads as they are very similar.

You have to show your attempts at answering the question before receiving help, this is a forum policy.

Have you tried to google?
ChemBuddy chemical calculators - stoichiometry, pH, concentration, buffer preparation, titrations.info, pH-meter.info, PZWT_s1

Sponsored Links